Managing the public during the nipah virus outbreak in Negeri Sembilan - ﻿Ramlee R. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
﻿The first Nipah virus outbreak was detected in Negeri Sembilan on 4th January 1999. It all started in Kampung Dato' Wong Seng Chow, Sikamat, in the district of Seremban. The outbreak was then identified as Japanese Encephalitis (JE). The machinery for control of JE was mobilised as soon as the outbreak in Perak was reported. That was done as early as 20th October 1998 with the collection of baseline data of all pig farms in the state. The state was put on alert and health education materials were produced and distributed. Among the communication challenges faced in controlling the outbreak were issues related to the handling of the pig farmers, workers, general public, the mass media, the encephalitis cases and their family members, non govermental organisations (NGO), health-care workers and other personels involved.